The Potential of Natural Propolis Extract Combined with Bovine Bone Graft in Increasing Heat Shock Protein 70 and Osteocalcin on Socket Preservation - Kresnoadi, Utari; Rahayu, Retno Pudji; Ariani, Maretaningtias Dwi; Soesanto, Soesanto (European Journal of Dentistry, 2020)
Objective This study aims to combine natural propolis with bovine bone graft (BBG) as a means of extraction socket preservation after 3 and 7 days toward expression of heat shock protein (HSP) 70 and osteocalcin to regenerate bone.Materials and Methods The Cavia cobaya were divided into eight groups, each consisting of seven samples. Their lower left incisors were extracted and induced with PEG, propolis extract, BBG, and a combination of propolis extract BBG. The research subjects were terminated on days 3 and 7 postextraction. Immunohistochemical and histopathological examinations were subsequently performed to observe HSP 70 expression, osteocalcin expression, osteoblasts, and osteoclasts. Statistical Analysis Data obtained were then analyzed with one-way analysis of variance (ANOVA) and Tukey’s honestly significant difference (HSD) tests.Results Both the groups with the combination of propolis extract and BBG on days 3 and 7 were found to present the highest number of HSP70 expression, osteocalcin expression, and osteoblast cells as well as the lowest number of osteoclasts.Conclusion Both the groups with the combination of propolis extract and BBG on days 3 and 7 were found to present the highest number of HSP70 expression, osteocalcin expression, and osteoblast cells as well as the lowest number of osteoclasts.
Keywords: propolis; bovine bone graft; heat shock protein 70; osteocalcin; bone regeneration